Level of Psychological Stress among Workers in Arab Hospitals in the City of Jerusalem - Makhlouf , Shadia Issa (Dirasat: Educational Sciences, 2022)
Objectives: This study aims to investigate the level of psychological stress among workers in Arab hospitals in the city of Jerusalem, Palestine. Methods: The study relied on a field descriptive approach. The study sample consisted of (143) individuals, chosen by a stratified random method, working in Arab hospitals in the city of Jerusalem. To achieve the objectives of the study, a questionnaire that consists of (25) paragraphs was designed. Results: The results indicate that the level of psychological stress among workers in Arab hospitals in the city of Jerusalem was moderate. It was also found that there are statistically significant differences at the level of significance (α ≥ 0.05) in the level of psychological stress among workers in Arab hospitals in the city of Jerusalem due to gender in favor of males. The results also show that there are no statistically significant differences at the significance level (α 0.05 ≥ ) in the level of psychological stress among workers in Arab hospitals in the city of Jerusalem due to qualification, years of service, age, marital status, or place of residence. Conclusions: Based on the above results, the researcher recommends conducting a study on the needs of male workers to help them overcome psychological pressures by preparing training programs.